К теории акустоэмиссии при неконсервативном движении ступеньки на винтовой дислокации - Локтев, В.М.; Халак, Ю.Н. (Видавничий дім "Академперіодика" НАН України, 2008)
The attempt is made to find a solution of the equations of motion for a continuous medium describing the driven displacement of a screw dislocation with jog in a crystal under the action of an ultrasonic wave. As a result, the sequence and the shape of acoustic emission pulses which can be studied experimentally are determined.